Ikonoklazem brez-umetnosti brezimnih - Osojnik, Iztok (Primerjalna književnost, 2016)
This article is a polemical analysis of the current state of the world and at the same time a manifesto. It considers the difference between the artistic creativity of the *everyday anonymous individual" that is artistically active, guided by the "event," and not by the neoliberal market ideology and the struggle for symbolic and material profit on the one hand, and its opposite: institutionalized art as a "capitalistic fetish." The article leans on the philosophy of Martin Heidegger to introduce a new syntagm: "the Iconoclastic Anonymity of Freedom-from-Art".
Keywords: art; umetnost; society; družba; kapitalizem; capitalism; neoliberalizem; kulturna industrija; ikonoklazem; netržna umetnost; ustvarjalnost; brezimnost; post-etika